Encapsulation of phenolic compounds by spray drying of Ancellotta and Aspirant Bouchet wines to produce powders with potential use as natural food colorants - Alvarez Gaona, Izmari Jasel (2022)
Ancellotta and Aspirant Bouchet, Vitis vinifera L., are wines with a high anthocyanin concentration that have been used to increase color in high-quality red wines. This work was focused on the encapsulation of Ancellotta (ANCE) and Aspirant Bouchet (AB) wines by spray drying and obtaining wine powders (WP) with a high concentration of phenolic compounds. Spray drying conditions were optimized and the phenolic compounds in the WP were characterized. All WP were evaluated for moisture content, water activity, color parameters, anthocyanins, and flavan-3-ols composition. There was no significant difference in total anthocyanins content of ANCE and AB WP when inlet air temperature increased from 135 to 145◦C with a fixed carrier concentration of 8% (w/w) but a decrease in the total anthocyanins was observed when carrier concentration increased to 10% (w/w). Regarding color evaluation, ANCE and AB WP corresponded to the fourth quadrant of color space CIELAB indicating blue - red color (348–357◦), characteristic of anthocyanins and wine. In general, the values of hueangle were not affected at higher percentages of carrier agent, consequently, an increase in the ratio carrier-wine did not lead to a dilution of material. These results indicate that inlet air temperature (in the selected range) did not influence the anthocyanin profile in the WP and has allowed for optimization of the conditions to obtain phenolic-rich colored powders with potential use as natural antioxidants and food colorants.